Mastering Metasploit : Take your penetration testing and IT security skills to a whole new level with the secrets of Metasploit, 3rd Edition /: Take your penetration testing and IT security skills to a whole new level with the secrets of Metasploit, 3rd Edition. (2018) - Jaswal, Nipun
No abstract available